Chikungunya (Togaviridae) and dengue 2 (Flaviviridae) viruses detected from Aedes aegypti mosquitoes in Burkina Faso by qRT-PCR technique: Preliminary results and perspective for molecular characterization of arbovirus circulation in vector populations - Hien, Aristide S.; Sangaré, Ibrahim; Ouattara, Eric L. Parfait; Sawadogo, Simon P.; Soma, Diloma D.; Maiga, Hamidou; Diabaté, Abdoulaye; Bonnet, Emmanuel; Ridde, Valéry; Fournet, Florence; Hawkes, Frances M.; Kaupra, Carina; et al. (Frontiers in Tropical Diseases, 2022)
In 2016, an entomological study was carried out in a railway transect between Banfora and Ouagadougou, Burkina Faso. The objective was to assess the risk factors of arbovirus outbreaks, including vector-borne infection status within representative regions of the country. Aedes aegypti mosquitoes were collected at the larval stage from their natural rearing habitats in four study sites when estimating the main larval index, then reared until adult stage and kept in RNAlater for the detection of arbovirus RNA. In the laboratory, mosquito samples were tested for dengue virus (DENV) and Chikungunya virus (CHIKV) using a real-time qRT-PCR stage. A DENV-2 positive pool was detected in Ouagadougou with a minimum infection rate (MIR) of 16.67 and other six CHIKV-positive pools with a MIR of 66.67 in Ouagadougou, Banfora, and Boromo. This qRT-PCR approach, if validated with various samples also comprising wild blood-fed adults, is a useful tool for arbovirus circulation and disease monitoring in Burkina Faso.